Focal myocarditis after mild COVID-19 infection in athletes - Nedeljkovic, I. P.; Giga, V.; Ostojic, M.; Djordjevic-Dikic, A.; Stojmenovic, T.; Nikolic, I.; Dikic, N.; Nedeljkovic-Arsenovic, O.; Maksimovic, R.; Dobric, M.; Mujovic, N.; Beleslin, B. (Diagnostics, 2021)
COVID-19 infection in athletes usually has a milder course, but in the case of complications, myocarditis and even sudden cardiac death may occur. We examined an athlete who felt symptoms upon returning to training after asymptomatic COVID-19 infection. Physical, laboratory, and echocardiography findings were normal. The cardiopulmonary exercise test was interrupted at submaximal effort due to severe dyspnea in the presence of reduced functional capacity in comparison to previous tests. Cardiac magnetic resonance (CMR) detected the focal myocarditis. After three months of recovery, CMR still revealed the presence of focal myocarditis and the persistence of decreased functional capacity. This case raises the question of screening athletes even after asymptomatic forms of COVID-19 infection.